Perspective of DGBL in ESL classroom among primary school teachers in Johor Bahru - Paramasivam, Tharani (2021)
The advancement of educational technology has crafted a pathway for the integration of various teaching methods that has been considered as a beneficial and effective tool for pupils. “Game-Based Learning” (GBL) is one of the teaching methods in assisting language teaching pedagogy. This initiation of language teaching pedagogy of using games at the nascent stage has led to the development of “digital game-based learning” (DGBL) as it incorporates “digital games” as a technological teaching kit in language learning environment. Past studies have revealed the utilization of “digital games” in in language learning process. However, limited research conducted on the usefulness of DGBL in ESL classroom, especially in Malaysia. Hence, the purpose of this study is to know teacher’s perspective on the usefulness of “Digital game-based learning” (DGBL) in ESL classroom among primary school teachers in Johor Bahru. The objectives of the study are to explore the teachers’ perspective on the usefulness of “Digital Game-Based Learning” (DGBL) in ESL classroom, to discover the teachers’ perspective on the barriers of “Digital Game-Based Learning” (DGBL) in ESL classroom and to find out the teachers’ perspective on the support needed to adopt “Digital Game-Based Learning” (DGBL) in ESL classroom. Case study research design was employed to know perspective of 9 ESL teachers in Johor Bahru. The data were collected from semi-structured interview, teacher’s journals, and observations. The findings of the study revealed usefulness of DGBL. Nonetheless, the study disclosed the barriers faced by teachers in utilising DGBL. Implications of the study revealed the role of school in achieving successful integration of DGBL in ESL classroom.